Investigating the antecedents of innovative behaviors in the hotel industry of Turkey - Sima Rahimizhian; Foad Irani (Tourism & Management Studies)
The growing focus on the benefits of innovative approaches to gain competitive advantages has inspired studies on the emergence of leadership styles that encourage employees to engage in innovative behaviors. This study examines the relationships between constructive leadership and employees' innovative behavior through the safety climate and employees' proactive behavior within the hospitality context. This paper considers constructive leaders as optimistic managers who regulate desired organizational outcomes with a genuine focus on the highest gains of employees and the organization. The person-environment fit (P–E fit) theory evaluated prominent organizational factors driving employees' innovative behavior. Two hundred seventy-two valid surveys were obtained among full-time employees of green hotels operating in Turkey. The proposed mediation model was analyzed using partial least squares structural equation modelling. According to the results, full-time employees of green Turkish hotels demonstrated improved, innovative behaviors at work, while a safe climate was paired with proactive behavior under constructive leadership supervision. The theoretical and managerial implications of findings, as well as recommendations for future research, are addressed.